Analysis of Stunting Risk Factors: Contribution of Immunization, Exclusive Breastfeeding, and Duration of Breastfeeding in a Cross-Sectional Study - Adnyana, I Gede Angga; Lubis, Nayna Aulia; Apriliana, Denta Haritsa; Kresnapati, I Nyoman Bagus Aji; Saputra, I Putu Bayu Agus (Lambung Mangkurat, 2025)
Stunting remains a major public health challenge in Indonesia, particularly in West Nusa Tenggara and North Lombok Regency. It is influenced by a combination of biological and environmental factors, with immunization history, exclusive breastfeeding (EBF), and breastfeeding duration being key modifiable determinants. This cross-sectional observational study examined the association between these factors and stunting among children aged 0–59 months. A total of 83 children were included in the analysis, with bivariate analysis conducted using the Chi-square test at a 95% confidence level (α = 0.05). Results showed that most children were male (59%), did not experience stunting (54.2%), received full immunization (67.5%), practiced EBF (83.15%), and were breastfed for less than 2 years (59.4%). No statistically significant association was found between immunization history (p=0.592) or EBF practices (p=0.219) and stunting. However, a significant relationship was identified between shorter breastfeeding duration (less than 2 years) and higher stunting risk (p=0.009, PR=2.62, 95% CI: 1.225–5.593). In conclusion, there was no significant relationship between the history of immunization and the history of exclusive breastfeeding with the incidence of stunting. However, there was a significant relationship between the duration of breastfeeding and the incidence of stunting